ANALISIS SWOT PENGEMBANGAN EKONOMI BERBASIS PERTANIAN DI DESA JAYAMUKTI, KECAMATAN LEUWISARI KABUPATEN TASIKMALAYA - Fauzan, Muhammad Rizky; Fadjarajani, Siti; Darmawan, Cahya (Jurnal Geografi, 2024)
Jayamukti Village, Leuwisari District, Tasikmalaya Regency, is an area with significant agricultural potential, especially supported by the dominance of irrigated rice fields. This research aims to analyze the potential for agricultural-based economic development in the village using land use maps as the main data. Analysis spatial is carried out to understand the distribution of agricultural land and other sectors, temporarily The SWOT approach is used to identify strengths, weaknesses, opportunities and threats in agricultural economic-based development. The research results show that Irrigated rice fields in Jayamukti Village have high productivity and can be developed become an agribusiness center. The main obstacles include limited market access and farmer capital small, while big opportunities lie in improving irrigation infrastructure and technology agriculture. This research recommendation includes increasing market access, technological innovation agriculture, as well as improving village infrastructure to support economic development sustainable.